2017
DOI: 10.1371/journal.pone.0187295
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dipeptidyl peptidase III from the human gut symbiont Bacteroides thetaiotaomicron

Abstract: Bacteroides thetaiotaomicron is a dominant member of the human intestinal microbiome. The genome of this anaerobe encodes more than 100 proteolytic enzymes, the majority of which have not been characterized. In the present study, we have produced and purified recombinant dipeptidyl peptidase III (DPP III) from B. thetaiotaomicron for the purposes of biochemical and structural investigations. DPP III is a cytosolic zinc-metallopeptidase of the M49 family, involved in protein metabolism. The biochemical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Both carboxyl oxygen atoms of Glu444 and Glu501 entered the Zn 2+ coordination sphere at the very beginning of MD simulations. Such behavior is inconsistent with all currently known crystallographic structures of AFO, 30 as well as with available crystallographic structures of the other DPP III family members, [33][34][35] and suggests an overestimate of electrostatic interactions (Supporting Information Figure S2). On other hand, the tetrahedral model developed by Pang 50 reproduced the active site architecture previously reported within the DPP III family to a certain degree.…”
Section: Zinc Ion Parametersmentioning
confidence: 65%
See 2 more Smart Citations
“…Both carboxyl oxygen atoms of Glu444 and Glu501 entered the Zn 2+ coordination sphere at the very beginning of MD simulations. Such behavior is inconsistent with all currently known crystallographic structures of AFO, 30 as well as with available crystallographic structures of the other DPP III family members, [33][34][35] and suggests an overestimate of electrostatic interactions (Supporting Information Figure S2). On other hand, the tetrahedral model developed by Pang 50 reproduced the active site architecture previously reported within the DPP III family to a certain degree.…”
Section: Zinc Ion Parametersmentioning
confidence: 65%
“…RMSD between the crystal structures of AFO and the closed structure of the human DPP III (PBD code: 3T6B) is about 1.0 Å. Both crystallographic and computational studies on DPPs III prove the existence of another conformation of the enzyme, the so‐called open form, with the two domains separated by a wide cleft . It is important to note that, in the case of the human orthologue, the open form is not catalytically active; both open and closed form exist in the solution, with the balance shifting toward the catalytically active closed form in the presence of a substrate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the transfer to have been from a bacterium to an animal means it happened to an ancestral metazoan and the mechanism is obscure; for the transfer to have been the other way around, implies frequent and recent gene sharing amongst bacteria. Family M49 (dipeptidyl-peptidase III) is found in animals; fungi; singlecelled organisms such as Dictyostelium, Leishmania (but not the closely related Trypanosoma), Paramecium, Tetrahymena, Giardia and Entamoeba; and bacteria mostly from the phylum Bacteriodetes (including the characterized dipeptidyl-peptidase IIIB from Bacteroides thetaiotaomicron, a component of the human intestinal flora) [53]. The homologues in bacteria are probably derived from horizontal gene transfers.…”
Section: Peptidase Families With An Origin In Bacteria and Eukaryotesmentioning
confidence: 99%
“…Both X-ray diffraction and MD simulations showed that the structure of the ligand free CaDPP III is much more compact than the ligand free structures of the other DPP III orthologues, which might be the reason for the signicantly higher K i value determined for tynorphin. 12,18,19,59…”
mentioning
confidence: 99%